Does chronic ankle instability patients lead to changes in biomechanical parameters associated with anterior cruciate ligament injury during landing? A systematic review and meta-analysis - He, Zhanyang; Zhu, Houwei; Ye, Binyong; Zheng, Zhe; Liu, Gongju; Pan, Huiju; Liu, Ronghua (Frontiers in Physiology, 2024)
Objective: This study aimed to determine if patients with chronic ankle instability (CAI) exhibit biomechanical changes associated with the increased risk of anterior cruciate ligament (ACL) injury during landing tasks.Study Design: This study was conducted through systematic review and meta-analysis.Data Sources: Searches were conducted in May 2024 across five electronic databases, including Web of Science, Scopus, PubMed, SPORTDiscus, and Cochrane Library.Eligibility Criteria: Studies were included if they (1) involved subjects with CAI and healthy controls and (2) assessed biomechanical variables such as ground reaction forces, joint angles, and joint torques. Results: Of the 675 identified studies, 171 were included in the review, and 13 were eligible for meta-analysis. The reviewed studies clearly defined research objectives, study populations, consistent participant recruitment, and exposures, and they used valid and reliable measures for outcomes.However, areas such as sample size calculation, study sample justification, blinding in assessments, and addressing confounders were not robust. This meta-analysis involved 542 participants (healthy group: n=251; CAI group: n=291). Compared with healthy individuals, patients with CAI exhibited a greater peak vertical ground reaction force (peak VGRF; SMD=0.30, 95% CI: 0.07-0.53, p=0.009), reduced hip flexion angles (SMD=-0.30, 95% CI: -0.51 to -0.17, p<0.0001), increased trunk lateral flexion (SMD=0.47, 95% CI: 0.05 to 0.9, p=0.03), greater hip extension moments (SMD=0.47, 95% CI: 0.09-0.84, p=0.02), and increased knee extension moments (SMD=0.39, 95% CI: 0.02-0.77, p=0.04).During landing tasks, patients with CAI demonstrate increased hip extension moments and knee extension moments, decreased hip flexion angles, increased peak VGRF, and increased trunk lateral flexion angles. These biomechanical variables are associated with an elevated risk of ACL injuries.